Preventive residual insecticide applications successfully controlled Aedes aegypti in Yucatan, Mexico - Gonzalo M. Vazquez-Prokopec; Azael Che-Mendoza; Oscar D. Kirstein; Wilberth Bibiano-Marin; Gabriela González-Olvera; Anuar Medina-Barreiro; Hector Gomez-Dantes; Norma Pavia-Ruz; Pablo Manrique-Saide (Scientific Reports, 2022)
Abstract Insecticide-based approaches remain a key pillar for Aedes-borne virus (ABV, dengue, chikungunya, Zika) control, yet they are challenged by the limited effect of traditional outdoor insecticide campaigns responding to reported arboviral cases and by the emergence of insecticide resistance in mosquitoes. A three-arm Phase II unblinded entomological cluster randomized trial was conducted in Merida, Yucatan State, Mexico, to quantify the entomological impact of targeted indoor residual spraying (TIRS, application of residual insecticides in Ae. aegypti indoor resting sites) applied preventively 2 months before the beginning of the arbovirus transmission season. Trial arms involved the use of two insecticides with unrelated modes of action (Actellic 300CS, pirimiphos-methyl, and SumiShield 50WG, clothianidin) and a control arm where TIRS was not applied. Entomological impact was quantified by Prokopack adult collections performed indoors during 10 min per house. Regardless of the insecticide, conducting a preventive TIRS application led to significant reductions in indoor Ae. aegypti densities, which were maintained at the same levels as in the low arbovirus transmission period (Actellic 300CS reduced Ae. aegypti density up to 8 months, whereas SumiShield 50WG up to 6 months). The proportional reduction in Ae. aegypti abundance in treatment houses compared to control houses was 50–70% for Actellic 300CS and 43–63% for SumiShield 50WG. Total operational costs including insecticide ranged from US$4.2 to US$10.5 per house, depending on the insecticide cost. Conducting preventive residual insecticide applications can maintain Ae. aegypti densities at low levels year-round with important implications for preventing ABVs in the Americas and beyond.